Towards Trustworthy Machine Learning Under Distribution Shifts - Wu, Jun (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Transfer learning aims to transfer knowledge or information from a source domain to a relevant target domain. It involves two key challenges: distribution shifts and trustworthiness concerns. Having these challenges in mind, my research focuses on understanding transfer learning from the perspective of knowledge transferability (e.g., IID and non-IID learning tasks) and trustworthiness (e.g., adversarial robustness, data privacy, and performance fairness).